UJI KONSENTRASI EKSTRAK DAUN SIRIH HUTAN BERPELARUT ORGANIK TERHADAP WERENG COKLAT - Rustam, Rusli; Mahardina, Arum Refsia (Jurnal Agroteknologi, 2024)
Rice is one of the priority food crop in Indonesia. The main problem faced by rice cultivation is the attack of brown planthopper (Nilaparvata lugens Stall.), this pest is one of the most important pest in rice cultivation, because it can cause a production decrease up to 100% by causing hopperburn symptoms and becoma a desease vector. Botanical pesticide of spiked pepper (Piper aduncum L.) can be the safe alternative to controling brown planthopper. This research aims to obtain effective concentration to controling brown planthopper. The research was conducted at The Plant Pest Laboratory Faculty of Agriculture and Organic Chemistry and Natural Materials Laboratory Faculty of Engineering, Riau University, from November 2020 to Januari 2021, using completely randomized design (CRD) consist of 6 treatments 4 replications. The treatment application consisted of concentrations of 0%, 0.20%, 0.40%, 0.60%, 0.80%, and 100% spiked pepper leaf methanol solvent extract. The result showed that different concentration significantly affected to the death of brown planthopper. Concentrations starting from 0.20% has good performance in killing pest, but the effective concentration to control brown planthoppers is 0.60% concentration of spiked pepper leaf methanol extract, with a total mortality of 82.50%, initial time of death 3.25 hours, and 50% time of death at 10 hours after application.